2023
DOI: 10.21203/rs.3.rs-2471354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neuroprotective effect of Clove essential oil against 6-OHDA-induced cell death in SH- SY5Y and a rat model of Parkinson's disease

Abstract: Parkinson's disease (PD) is the second most prevalent neurological disorder. Natural therapies are becoming more popular for preventing disease onset. Clove essential oil (CEO), a potent antioxidant derived from Syzygium aromaticumbuds, was tested in vitro (SH-SY5Y) and in vivo (PD rat model) for its ability to protect against 6-OHDA-induced cell death. Twenty-four hours of SH-SY5Y cells' exposure to 6-OHDA (100 µM) drastically decreased cell viability. At doses lesser than 20 µg/ml, CEO and its main component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…For example, CF was highest in phenolics, flavonoids, and nitrogen (DPPH) free radical scavenging capacities and significantly prevented H 2 O 2 -induced cell death. This is consistent with a previous study that reported that clove essential oil and its major component, eugenol, were protective against 6-hydroxdopamine (OHDA)-induced cell death in SH-SY5Y cells [ 77 ]. In addition, Liu et al [ 78 ] also reported that clove had higher total phenolic content, flavonoid content, and DPPH scavenging capacity than the majority of 68 Chinese herbal samples tested, including black pepper.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, CF was highest in phenolics, flavonoids, and nitrogen (DPPH) free radical scavenging capacities and significantly prevented H 2 O 2 -induced cell death. This is consistent with a previous study that reported that clove essential oil and its major component, eugenol, were protective against 6-hydroxdopamine (OHDA)-induced cell death in SH-SY5Y cells [ 77 ]. In addition, Liu et al [ 78 ] also reported that clove had higher total phenolic content, flavonoid content, and DPPH scavenging capacity than the majority of 68 Chinese herbal samples tested, including black pepper.…”
Section: Discussionsupporting
confidence: 93%
“…R8 was the only sample that did not reduce cell viability at any concentration; however, pre-treatment with R8 did not significantly improve cell viability in the presence of H 2 O 2 -induced oxidative stress. Several studies have found that phenolic extracts reduce cell viability in the absence of a stressor; for example, Dhanalakshmi et al [ 75 ] found that vanillin, a natural phenolic compound, reduced cell viability at concentrations >1 μM and Hamdi et al [ 77 ] found that clove essential oil was toxic at concentrations >40 μg/mL. Together with the existing studies, these results suggest that plant-derived extracts administered directly to cells without a stressor can have differential effects despite being protective in the presence of a physiological stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subsequent cell culture experiments were conducted using concentrations below 50 µg/mL to minimize cell death due to the extract's toxicity. Similar results were obtained in a previous study where no cytotoxicity was observed up to 20 µg/mL when treating SH-SY5Y cells with the clove essential oil [43]. The pure compounds were tested at lower concentrations (0.01, 0.1, 1, 10 µg/mL), where eugenol and TMA displayed significant (* p < 0.05) decreases in cell viability (89.9% and 87.2%, respectively) compared to the control at 10 µg/mL.…”
Section: Noncytotoxic Effect Of Clove Extracts On the Sh-sy5y Cell Linesupporting
confidence: 91%
“…Sci. 2023,24, x FOR PEER REVIEW 8 of 26 cells with the clove essential oil[43]. The pure compounds were tested at lower concentrations (0.01, 0.1, 1, 10 µg/mL), where eugenol and TMA displayed significant (* p < 0.05) decreases in cell viability (89.9% and 87.2%, respectively) compared to the control at 10 µg/mL.…”
mentioning
confidence: 99%